Gut microbiota: key facilitator in metastasis of colorectal cancer - Yu, Siyi; Wang, Shuyi; Xiong, Bin; Peng, Chunwei (Frontiers in Oncology, 2023)
Colorectal cancer(CRC)ranks third in terms of incidence among all kinds of cancer.The main cause of death is metastasis. Recent studies have shown that the gut microbiota could facilitate cancer metastasis by promoting cancer cells proliferation, invasion, dissemination, and survival. Multiple mechanisms have been implicated, such as RNA-mediated targeting effects, activation of tumor signaling cascades, secretion of microbiota-derived functional substances, regulation of mRNA methylation, facilitated immune evasion, increased intravasation of cancer cells, and remodeling of tumor microenvironment (TME). The understanding of CRC metastasis was further deepened by the mechanisms mentioned above. In this review, the mechanisms by which the gut microbiota participates in the process of CRC metastasis were reviewed as followed based on recent studies.